Athletic performance decline over the life span: Cross-sectional and longitudinal analyses of elite and masters track-and-field data - Pfeifer, B.; Nelson, W. B.; Hyldahl, R. D. (International Journal of Sports Physiology and Performance, 2024)
Purpose Loss of muscle power has a significant impact on mobility in geriatric populations, so this study sought to determine the extent and time course of performance decline in power-centric events throughout the life span via retrospective analyses of masters and elite track-and-field data.